Blockchain and Electronic Health Records Security in Hospitals: Blockchain and Electronic Health Records Security in Hospitals - Van Nhan Nguyen; Thúy Vân, Trần Thí (Information Technology and Systems, 2025)
Blockchain is a block chain technology with a complex encryption process, featuring security, decentralization and privacy. Thanks to its ability to authenticate data accurately and minimize the risk of fraud, Blockchain has been applied in many industries, including healthcare, in medical examination and treatment processes and record management. Storing medical and health records in digital form helps to retrieve information quickly, improve the quality of patient care and the effectiveness of medical examination and treatment. However, the issue of online information security is still a major concern for managers, patients and users. This article will present (1) the operating mechanism of Blockchain; (2) the medical examination and treatment process according to regulations; (3) the security of health records and medical records when applying Blockchain technology, and propose solutions in the application of health records and patient medical records management.